1988
DOI: 10.1126/science.2971269
|View full text |Cite
|
Sign up to set email alerts
|

The SCID-hu Mouse: Murine Model for the Analysis of Human Hematolymphoid Differentiation and Function

Abstract: The study of human hematopoietic cells and the human immune system is hampered by the lack of a suitable experimental model. Experimental data are presented showing that human fetal liver hematopoietic cells, human fetal thymus, and human fetal lymph node support the differentiation of mature human T cells and B cells after engraftment into mice with genetically determined severe combined immunodeficiency. The resultant SCID-hu mice are found to have a transient wave of human CD4+ and CD8+ T cells and human Ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
717
2
4

Year Published

1996
1996
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,306 publications
(732 citation statements)
references
References 41 publications
9
717
2
4
Order By: Relevance
“…[19][20][21] Briefly, femurs, tibias and fibulas of 17-to 18-gestational-week-old fetuses (Advanced Bioscience Resources; Alameda, CA, USA) were implanted subcutaneously into 6-8 week-old mice. After 4 weeks, patient bone marrow cells in PBS supplemented with 25% high protein Matrigel (BD Biosciences) were transplanted directly into human bone grafts.…”
Section: Flow Cytometric Analysismentioning
confidence: 99%
“…[19][20][21] Briefly, femurs, tibias and fibulas of 17-to 18-gestational-week-old fetuses (Advanced Bioscience Resources; Alameda, CA, USA) were implanted subcutaneously into 6-8 week-old mice. After 4 weeks, patient bone marrow cells in PBS supplemented with 25% high protein Matrigel (BD Biosciences) were transplanted directly into human bone grafts.…”
Section: Flow Cytometric Analysismentioning
confidence: 99%
“…To confirm our in vitro results in the human in vivo system, we used mice with severe combined immunodeficiency (SCID). Recent studies have demonstrated that the SCID mouse has several defects in both humoral and cellmediated immunity, and can serve as a recipient of grafts derived from a variety of human tissues, [22][23][24][25][26][27] including rheumatoid synovium. Thus, proliferative rheumatoid synovium can grow as a xenograft in SCID mice and pre- serve the histologic components of rheumatoid synovia.…”
Section: Figure 4 Immunohistochemical Analysis Of the Effects Of Hfasmentioning
confidence: 99%
“…The severe combined immunodeficient (SCID)-hu Thy/Liv mouse has an intact human thymus organ, thus allowing investigation of HIV-1 pathogenesis in a human lymphoid organ. [4][5][6] However, very low levels of human T cells are detected in the peripheral lymphoid organs or blood. The hu-peripheral blood lymphocyte (PBL)-SCID mouse supports transient and selective engraftment of xenoreactive human T cells.…”
mentioning
confidence: 99%